Pengaruh Gaya Kepemimpinan Kepala Sekolah dan Motivasi Kerja Terhadap Kinerja Guru di Sekolah Dasar (SD) Negeri Gugus Sihoum Kecamatan Indrapuri Kabupaten Aceh Besar - Juliana, Juliana; Musdiani, Musdiani; Zahraini, Zahraini (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the influence of the principal's participative leadership style and teacher work motivation together on teacher performance in SD Negeri Sihoum Cluster, Indrapuri District, Aceh Regency. This research uses a quantitative approach with expost facto method. The independent variable in this study is the principal's participative and teacher work motivation, and the dependent variable is teacher performance. The data collection technique used is questionnaires. The type of data analysis used is multiple regression analysis. The results proved that the partial correlation between the principal's leadership style (X1) and teacher performance (Y) when work motivation (X2) was considered constant was 0.556 and the partial correlation between work motivation (X1) and teacher performance (Y) when the principal's leadership style (X1) was considered constant was 0.040. Thus, it can be concluded that the higher the principal's leadership style and work motivation, the better the performance of teachers in SD Negeri Sihoum Cluster, Indrapuri District, Aceh Besar Regency